Fluxional Bonds in Planar B 19 − , Tubular Ta@B 20 − , and Cage‐Like B 39 - Yan, Miao; Li, Hai‐Ru; Zhao, Xiao‐Yun; Lu, Xiao‐Qin; Mu, Yue‐Wen; Lu, Hai‐Gang; Li, Si‐Dian (Journal of computational chemistry, 2019)
Based on detailed bonding analyses on the fluxional behaviors of planar B 19 − , tubular Ta@B 20 − , and cage‐like B 39 − , we propose the concept of fluxional bonds in boron nanoclusters as an extension of the classical localized bonds and delocalized bonds in chemistry. © 2018 Wiley Periodicals, Inc.